CPUE STANDARDIZATION OF FRIGATE TUNA (Auxis thazard) CAUGHT BY PURSE SEINE IN THE WESTERN SUMATERA COAST (FMA 572) - Ririk Kartika Sulistyaningsih; Irwan Jatmiko; Maya Agustina (Indonesian Fisheries Research Journal, 2020)
Frigate tuna (Auxis thazard) is one of the major commercial tuna species, both in industrial and small scale fisheries, particularly in the waters off Western Sumatera. In Indonesia, A. thazard is a group of locally called “tongkol” together with A. rochei, Thunnus tonggol, and Euthynnus affinis. This study describes a preliminary examination of frigate tuna catch from purse seine off the coast of western Sumatera (FMA 572). The data were collected daily by an enumerator on the fish landing site from 2013 to 2017, including fishing gear, number of days at sea, catch, length, and weight of frigate tuna. The fishing ground coordinate data provided by the observer on board the vessel. General Linear Model (GLM) with gamma was applied in this study to standardize the CPUE by year, quarter, season, and GT as fixed variables. The results showed that the variation of CPUE was mostly influenced by year and quarter, while season and fleet size (GT) showed less impact on the catch. In general, even though the catch trend declines during the observation years, the population of frigate tuna off the coast of western Sumatera (FMA 572) were considered sustainable.